1986
DOI: 10.1111/j.1365-3083.1986.tb02194.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Tumour Necrosis Factor‐Like Cytotoxicity in Serum from Patients With Septicaemia but Not from Untreated Cancer Patients

Abstract: With a bioassay sensitive for recombinant tumour necrosis factor at a concentration of 10(-4) ng/ml, we were able to detect tumour necrosis factor-like cytotoxicity in serum from three patients in the initial phase of septicaemia. The cytotoxic activity corresponded to a concentration of recombinant tumour necrosis factor of 2 X 10(-2)-3 X 10(-3) ng/ml serum. The concentration in cerebrospinal fluid was estimated to be three times higher than in serum. In 23 untreated patients with malignant disease of varying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
1

Year Published

1987
1987
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(32 citation statements)
references
References 10 publications
2
29
0
1
Order By: Relevance
“…The observations concerning the presence of TNF and IL-1 in the serum of cancer patients are inconsistent, however. Moldawer et al (1988) could not detect IL-1 and TNF bioactivities in the plasma of weight-losing cancer patients; other investigators have made similar observations (Scuderi et al, 1986;Waage et al, 1986;Selby et al, 1987;Socher et al, 1988b). By contrast, the presence of TNF has been observed in the serum of children with acute lymphoblastic leukaemia (Saarinen et al, 1990), in other cancer patients (Aderka et al, 1985;Balkwill et al, 1987), and in cachectic tumourbearing rats (Stovroff et al, 1989).…”
Section: Humoral Mediatorsmentioning
confidence: 82%
“…The observations concerning the presence of TNF and IL-1 in the serum of cancer patients are inconsistent, however. Moldawer et al (1988) could not detect IL-1 and TNF bioactivities in the plasma of weight-losing cancer patients; other investigators have made similar observations (Scuderi et al, 1986;Waage et al, 1986;Selby et al, 1987;Socher et al, 1988b). By contrast, the presence of TNF has been observed in the serum of children with acute lymphoblastic leukaemia (Saarinen et al, 1990), in other cancer patients (Aderka et al, 1985;Balkwill et al, 1987), and in cachectic tumourbearing rats (Stovroff et al, 1989).…”
Section: Humoral Mediatorsmentioning
confidence: 82%
“…However, the degree of wasting in the cancer patients used in the study was not noted, although patients ranged from those in remission to ones with advanced disease. Other workers have not found increased TNF in cancer patients [19].…”
Section: Discussionmentioning
confidence: 99%
“…TNF levels in the remaining samples ranged in general from 2 to 300 pg/ml, and all of the patients (5/79) with TNF levels > 0.1 ng/ml died (70). In an earlier study, 3/23 septic patients were found to have TNF levels of 3-20 pg/ml (71). Tracy et al employed a skeletal muscle depolarization assay to detect picomolar levels of TNF in plasma samples of critically ill patients (72,73).…”
Section: Discussionmentioning
confidence: 99%